EDUKASI MENGENAI BULLYING TERHADAP SISWA SMP YP PGRI DISAMAKAN KOTA MAKASSAR - Adhim Vayla Rahmadio Mijaya; Astiti Tenriawaru Ahmad; Amirah Aminanty Agussalim; Nurfajriyanti Rasyid; Audri Damayanti; Ince Ayu Anggriani Rizal (Universitas Negeri Makassar, 2023)
This activity is a psychoeducational activity in order to increase students' knowledge regarding the dangers of bullying, forms of bullying, causes and effects of bullying, and how to prevent and deal with bullying. The background of this activity is because bullying is a problem that often occurs in society, especially teenagers who are in junior high and high school. The purpose of this activity is to provide knowledge to SMP YP PGRI students regarding bullying. The benefit of this activity is that it increases the knowledge of SMP YP PGRI students about the dangers of bullying. The targets of this activity are teenagers who are currently in class VII of junior high school, either those who have experienced bullying or who have never experienced bullying. This activity was carried out using the psychoeducation method, where before the implementation of psychoeducation the participants chose a pre-test to measure the extent of their initial understanding regarding the material provided, and after being given psychoeducation, students were asked again to choose a posttest to see whether or not there was a change in understanding. Then proceed with giving games to once again measure students' understanding of the material that has been given.Kegiatan ini merupakan kegiatan psikoedukasi dalam rangka meningkatkan pengetahuan siswa terkait bahaya bullying, bentuk-bentuk bullying, sebab dan akibat bullying, serta cara mencegah dan menangani bullying. Latar belakang dari kegiatan ini karena bullying menjadi masalah yang sering terjadi masyarakat, terutama remaja-remaja yang duduk di bangku SMP dan SMA. Tujuan dari kegiatan ini untuk memberikan pengetahuan kepada siswa SMP YP PGRI terkait bullying. Manfaat dari kegiatan ini yaitu meningkatnya pengetahuan siswa SMP YP PGRI mengenai bahaya dari bullying. Sasaran dalam kegiatan ini adalah remaja yang saat ini duduk di bangku SMP kelas VII baik yang pernah mengalami tindakan bullying ataupun yang tidak pernah mengalami tindakan bullying. Kegiatan ini dilakukan dengan metode pemberian psikoedukasi, di mana sebelum pelaksanaan psikoedukasi peserta mengisi pre-test untuk mengukur sejauh mana pemahaman awal terkait materi yang diberikan, dan setelah diberi psikoedukasi, siswa diminta lagi untuk mengisi posttest untuk melihat ada atau tidaknya perubahan pemahaman. Kemudian dilanjutkan dengan pemberian games untuk sekali lagi mengukur pemahaman siswa terkait materi yang telah diberikan.